2024
DOI: 10.5194/egusphere-2024-1004
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An overview of outdoor low-cost gas-phase air quality sensor deployments: current efforts, trends, and limitations

Kristen Okorn,
Laura T. Iraci

Abstract: Abstract. We reviewed 60 sensor networks and 15 related efforts (sensor review papers and data accessibility projects) to better understand the landscape of stationary low-cost gas-phase sensor networks deployed in outdoor environments worldwide. This study is not exhaustive of every gas-phase sensor network on the globe, but rather exists to categorize types of sensor networks by their key characteristics and explore general trends. This also exposes gaps in monitoring efforts to date, especially regarding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 131 publications
0
1
0
Order By: Relevance
“…The application of low-cost air quality monitoring networks has substantially grown over the last decade because of technological advances in the production of cheap and portable air pollution sensors [19][20][21][22][23][24]. Recent review papers [25,26] analysed practical aspects of outdoor air quality low-cost sensor networks, focusing on gas pollutant networks (analysed a total of 60 LCS networks targeting outdoor environments all over the world) and Carotenuto et al [26] including both gas and PM sensor networks. In the open-access literature, Carotenuto et al identified a total of 111 low-cost air quality monitoring networks for campaigns that had a duration from 3 months up to 4 years that were performed in the period 2014-2022.…”
Section: Introductionmentioning
confidence: 99%
“…The application of low-cost air quality monitoring networks has substantially grown over the last decade because of technological advances in the production of cheap and portable air pollution sensors [19][20][21][22][23][24]. Recent review papers [25,26] analysed practical aspects of outdoor air quality low-cost sensor networks, focusing on gas pollutant networks (analysed a total of 60 LCS networks targeting outdoor environments all over the world) and Carotenuto et al [26] including both gas and PM sensor networks. In the open-access literature, Carotenuto et al identified a total of 111 low-cost air quality monitoring networks for campaigns that had a duration from 3 months up to 4 years that were performed in the period 2014-2022.…”
Section: Introductionmentioning
confidence: 99%